Does tourism lead to environmental impact? cross-national static and dynamic evidence from the ecological footprint - A. Jaz, Nur Ameera; Habibullah, Muzafar Shah; Wan Ngah, Wan Azman Saini; Kaliappan, Shivee Ranjanee (UM Press, 2023)
At present, public consciousness on respecting and safeguarding the environment is declining rapidly. On that note, this study assumes that growing tourism has negative environmental implications. To satisfy tourism demand, overconsumption, and overexploitation through the development of tourism-related facilities have generated waste that destroy ecosystem functions. Ecological footprint is used to study the environmental impact of tourism activities by including the role of governance in our model. The outcome reveals that the environment is significantly affected by tourism pressure and good governance is essential for environmental protection.